Case definition for progressive multifocal leukoencephalopathy following treatment with monoclonal antibodies. Issue 9 (17th July 2012) - Mentzer, Dirk; Prestel, Jürgen; Adams, Ortwin; Gold, Ralf; Hartung, Hans-Peter; Hengel, Hartmut; Kieseier, Bernd C; Ludwig, Wolf-Dieter; Keller-Stanislawski, Brigitte
Abstract : Background: Novel immunosuppressive/modulating therapies with monoclonal antibodies (MABs) have been associated with progressive multifocal leukoencephalopathy (PML), a potentially fatal disease of the brain caused by the JC virus. Taking the complex diagnostic testing and heterogeneous clinical presentation of PML into account, an agreed case definition for PML is a prerequisite for a thorough assessment of PML. Objective/methods: A working group was established to develop a standardised case definition for PML which permits data comparability across clinical trials, postauthorisation safety studies and passive postmarketing surveillance. The case definition is designed to define levels of diagnostic certainty of reported PML cases following treatment with MABs. It was subsequently used to categorise retrospectively suspected PML cases from Germany reported to the Paul-Ehrlich-Institute as the responsible national competent authority. Results: The algorithm of the case definition is based on clinical symptoms, PCR for JC virus DNA in cerebrospinal fluid, brain MRI, and brain biopsy/autopsy. The case definition was applied to 119 suspected cases of PML following treatment with MABs and is considered to be helpful for case ascertainment of suspected PML cases for various MABs covering a broad spectrum of indications. Even if the available information is not yet complete, the case definition provides a level of diagnostic certainty. Conclusions: The proposed case definition permits data comparability among different medicinal products and among active as well as passive surveillance settings. It may form a basis for meaningful risk analysis and communication for regulators and healthcare professionals.